2017
DOI: 10.1186/s12984-017-0252-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of unilateral real-time biofeedback on propulsive forces during gait

Abstract: BackgroundIn individuals with post-stroke hemiparesis, reduced push-off force generation in the paretic leg negatively impacts walking function. Gait training interventions that increase paretic push-off can improve walking function in individuals with neurologic impairment. During normal locomotion, push-off forces are modulated with variations in gait speed and slope. However, it is unknown whether able-bodied individuals can selectively modulate push-off forces from one leg in response to biofeedback. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 34 publications
0
26
0
2
Order By: Relevance
“…An increase in absolute swing time and overall stride time seemed to be necessary consequences when increasing absolute stance time with feedback. Previous studies have demonstrated unilateral propulsive biofeedback induces changes in the targeted limb only for both people with and without stroke [35, 36], but a prosthesis presents different challenges. Additionally, amputees may have less control over the prosthesis timing because the control parameters (related to swing flexion/extension timing) were fixed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in absolute swing time and overall stride time seemed to be necessary consequences when increasing absolute stance time with feedback. Previous studies have demonstrated unilateral propulsive biofeedback induces changes in the targeted limb only for both people with and without stroke [35, 36], but a prosthesis presents different challenges. Additionally, amputees may have less control over the prosthesis timing because the control parameters (related to swing flexion/extension timing) were fixed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…On a further note, several previous studies investigate the collection of key kinematics and kinematic information, including joint angle, trajectory of center of mass, ground reaction force, during gait, and so on using the smallest possible inertial sensors [41,45]. Meanwhile, gait training using biofeedback of propulsion force on gait velocity and TLA could improve gait performance [18,[46][47][48]; however, these methods are not easily reproduced in clinical practice due to their complicated environmental restrictions. e ndings of this study can contribute towards establishing a more clinically friendly method for gait assessment as well as biofeedback gait training in clinical practice.…”
Section: Similarity Of Tla Measured By Imu and Motion Analysismentioning
confidence: 99%
“…Third, it is possible that the subject did not try to minimize propulsive force asymmetry when relearning to walk. A potentially insightful experiment would be to provide the subject with real-time feedback of his propulsive force asymmetry and instruct him to attempt to minimize it, similar to recent studies performed on healthy individuals (Schenck and Kesar, 2017) and individuals post-stroke (Genthe et al, 2018). Such an experiment could elucidate whether the subject's propulsive force asymmetry is primarily due to neural control limitations, biomechanical constraints, or a subconscious decision to optimize other quantities (e.g., metabolic cost Zarrugh et al, 1974; Bertram, 2005).…”
Section: Discussionmentioning
confidence: 99%